Evaluación de la Gestión Financiera y su incidencia en la rentabilidad, de la empresa Zapatería Yuly periodo 2013 - Ríos Ramírez, Jan Marcos (2015)
Assess the financial management and its impact on the profitability of the company Zapatería Yuly city of Tarapoto, 2013 period was paramount. The research method was Deductive-Inductive since in him a hypothesis that is deductively or inductively analyzed and subsequently verified experimentally, sought the theoretical part does not lose its meaning, so the theory was later associated with was raised reality. Deductive method was applied because it corresponds to a single company "Shoe Yuly", it understood the general study of the corresponding company retail sale of textile, Footwear. Financial management involves the realization of financial policies, by implementing strategies, tactics, processes, procedures, techniques and appropriate for the effective management of financial resources financial practices. Financial management in the Shoe Yuly Company Tarapoto, 2013, was poor because of the twenty (22) activities to do both activities decisions investment, financing and resource management, will only be executed six (6), achieved only 27% of activities, these shortcomings had a negative impact on profitability indicators.